Эвалюцыя пахавання «нячыстых» нябожчыкаў у ХХ – пачатку ХХІ стагоддзя (па матэрыялах беларусаў Падзвіння) - Аўсейчык, У. Я. (Мінск : Права і эканоміка, 2011)
В статье на основе материалов белорусов Придвинья рассматривается эволюция погребального обряда «нечистых» покойников, а также представлений связанных с их погребением, на протяжении ХХ – нач. ХХI в. Особое внимание уделено анализу изменений в погребении таких категорий «нечистых» покойников как некрещеные дети, самоубийцы и колдуны = The evolution of funeral ceremony of the “un-pure” dead men and representations connected with their burial during the 20th-beginning of the 21th centuries are examined in the article on the basic of materials of Belarusians of Dvina region. A special attention is given to the analysis of the changes in the burial ceremonies of such categories of the “un-pure” dead men as not-christen children, suicides and warlocks